Daya Hambat Ekstrak Kalsium Karbonat (CaCO3) dari Limbah Cangkang Telur Bebek (Anas platyrhynchos domesticus) terhadap Pertumbuhan Bakteri streptococcus mutans - Mila Febriany; Kurniaty Pamewa; Rini Pratiwi; Andy Fairuz Zuraida Eva; Nur Aqilah (Jurnal Anestesi, 2026)
Good oral and dental health is essential for improving quality of life and human productivity. Dental caries is a chronic disease that develops gradually, beginning with the appearance of white spots caused by plaque accumulation. Plaque forms due to the activity of microorganisms such as Streptococcus mutans, which plays a role in lowering the pH of the oral cavity, thereby triggering tooth demineralization. Eggshells contain calcium carbonate and other compounds with antibacterial nanoparticle properties. These components have the potential to inhibit bacterial growth, including Streptococcus mutans, and may serve as an alternative for preventing dental caries through plaque control and oral pH regulation. The aim of this study was to determine the inhibitory effect of calcium carbonate extract derived from duck eggshell waste (Anas platyrhynchos domesticus) against Streptococcus mutans. This research employed an experimental laboratory method with statistical analysis using One-Way ANOVA. The samples in this study consisted of five concentrations: 15%, 20%, 25%, 30%, and 35%. The results showed that all concentrations exhibited strong inhibitory activity against Streptococcus mutans. In conclusion, the alternative hypothesis of this study was accepted, and the findings demonstrated that concentrations of 15%, 20%, 25%, 30%, and 35% showed a significant increase in effectiveness. This indicates that calcium extract from duck eggshells (Anas platyrhynchos domesticus) contains bioactive compounds capable of inhibiting the growth of Streptococcus mutans.